(3QSGdI aj GdYed HGdQHY GdeLjHs - (3eMeO Hf eMeO Hf CHj GdaJM GdUhaj GdTGaYjs
(3ChdgG (B:s
(3bGd GdTjN GdGeGe GdMeO ddg GdeJaQO HUaGJ GdceGd hHYO agPg QSGdI Ydi GdQHY GdeLjH SejJgG GdTeSjI ai GdCYeGd GdLjHjI s
(3BNQgG (B:s
(3Ch bSefG bGeI GdTNU Ydi Xdg hVQHfG GdMGUd ai Xd GdSMGHI NQL HYOgG Yf GdGQV cGdChd hGddg CYde JeJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9242) s
Keywords: (3Gdadcs